Reducing emissions from agriculture to meet the 2 °C target. (11th July 2016) - Wollenberg, Eva; Richards, Meryl; Smith, Pete; Havlík, Petr; Obersteiner, Michael; Tubiello, Francesco N.; Herold, Martin; Gerber, Pierre; Carter, Sarah; Reisinger, Andrew; van Vuuren, Detlef P.; Dickie, Amy; et al.
Abstract: More than 100 countries pledged to reduce agricultural greenhouse gas (GHG) emissions in the 2015 Paris Agreement of the United Nations Framework Convention on Climate Change. Yet technical information about how much mitigation is needed in the sector vs. how much is feasible remains poor. We identify a preliminary global target for reducing emissions from agriculture of ~1 GtCO2 e yr −1 by 2030 to limit warming in 2100 to 2 °C above pre‐industrial levels. Yet plausible agricultural development pathways with mitigation cobenefits deliver only 21–40% of needed mitigation. The target indicates that more transformative technical and policy options will be needed, such as methane inhibitors and finance for new practices. A more comprehensive target for the 2 °C limit should be developed to include soil carbon and agriculture‐related mitigation options. Excluding agricultural emissions from mitigation targets and plans will increase the cost of mitigation in other sectors or reduce the feasibility of meeting the 2 °C limit.